Pengaruh Penggunaan Gumuk Pasir Sumalu Sebagai Agregat Halus Pada Campuran Beton Menggunakan Superplasticizer - Filbert Sanfra Restu; Jonie Tanijaya; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Sanddunes are a natural formation due to wind processes called aeolean morphology. Sumalu sandbank has rather hard grains like river sand and is purplish ash. Sumalu sand predominantly contains silica which is a good aggregate binder, this is the same as the function of cement in a concrete mixture. Superplasticizer is classified as an additional material to increase workability, where when providing additional materials Superplasticizer moisture content in concrete can be reduced without reducing workability. The coarse aggregate of this test comes from the Jeneberang river and the fine aggregate comes from Sumalu. The method used is Mix Design SNI 03-2834-2000. The compressive strength of the concrete was tested when the specimens were 7, 14 and 28 days old. The compressive strength values ​​of concrete at 28 days for normal concrete, variations of 0.5%, 1.0% and 1.5% are 25,821 MPa, 26,289 MPa, 25,392 MPa and 24,752 MPa. The results obtained from the tests were that the average concrete flexural strength values ​​for normal concrete and variations of 0.5%, 1.0% and 1.5% were 2.921 MPa, 3.173 MPa, 2.619 MPa and 2.166 MPa. From the test results, the average theoretical modulus of elasticity values in normal concrete and variations of 0.5%, 1.0% and 1.5% are 23882.753 MPa, 24098.216 MPa, 23683.522 MPa, 23383.149 MPa.